Theft in an ultimatum game: chimpanzees and bonobos are insensitive to unfairness - Kaiser, Ingrid (Biology letters, 2012)
Humans, but not chimpanzees, punish unfair offers in ultimatum games, suggesting that fairness concerns evolved sometime after the split between the lineages that gave rise to Homo and Pan. However, nothing is known about fairness concerns in the other Pan species, bonobos. Furthermore, apes do not typically offer food to others, but they do react against theft. We presented a novel game, the ultimatum theft game, to both of our closest living relatives. Bonobos and chimpanzee ‘proposers’ consistently stole food from the responders' portions, but the responders did not reject any non-zero offer. These results support the interpretation that the human sense of fairness is a derived trait.